RNA-Targeting CRISPR/CasRx system relieves disease symptoms in Huntington’s disease models - Yingqi Lin; Caijuan Li; Yizhi Chen; Jiale Gao; Jiawei Li; Chunhui Huang; Zhaoming Liu; Wei Wang; Xiao Zheng; Xichen Song; Jianhao Wu; Jiaxi Wu; et al. (Molecular Neurodegeneration)
Abstract Background HD is a devastating neurodegenerative disorder caused by the expansion of CAG repeats in the HTT. Silencing the expression of mutated proteins is a therapeutic direction to rescue HD patients, and recent advances in gene editing technology such as CRISPR/CasRx have opened up new avenues for therapeutic intervention. Methods The CRISPR/CasRx system was employed to target human HTT exon 1, resulting in an efficient knockdown of HTT mRNA. This therapeutic effect was substantiated in various models: HEK 293 T cell, the HD 140Q-KI mouse, and the HD-KI pig model. The efficiency of the knockdown was analyzed through Western blot and RT-qPCR. Additionally, neuropathological changes were examined using Western blot, immunostaining, and RNA sequencing. The impact on motor abilities was assessed via behavioral experiments, providing a comprehensive evaluation of the treatment's effectiveness. Results CRISPR/CasRx system can significantly reduce HTT mRNA levels across various models, including HEK 293 T cells, HD 140Q-KI mice at various disease stages, and HD-KI pigs, and resulted in decreased expression of mHTT. Utilizing the CRISPR/CasRx system to knock down HTT RNA has shown to ameliorate gliosis in HD 140Q-KI mice and delay neurodegeneration in HD pigs. Conclusions These findings highlight the effectiveness of the RNA-targeting CRISPR/CasRx as a potential therapeutic strategy for HD. Furthermore, the success of this approach provides valuable insights and novel avenues for the treatment of other genetic disorders caused by gene mutations.